2004
DOI: 10.1007/s00223-004-0286-7
|View full text |Cite
|
Sign up to set email alerts
|

Seven Years of Treatment with Risedronate in Women with Postmenopausal Osteoporosis

Abstract: The effects of 7 years of risedronate treatment were evaluated in a second 2-year extension of a 3-year vertebral fracture study in women with osteoporosis. For the first 5 years of the study, women received risedronate 5 mg/day or placebo according to the original randomization, with maintenance of blinding. All the women who entered into the 6-7 years extension study received risedronate 5 mg/day. Endpoints included vertebral and nonvertebral fracture assessments, changes in biochemical markers of bone turno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
156
3
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(179 citation statements)
references
References 12 publications
8
156
3
12
Order By: Relevance
“…Recently, however, it has been reported that suppressed bone turnover by long-term treatment with high-dose risedronate increased microdamage accumulation in the dog rib [11], suggesting long-term and/or high-dose risedronate treatment may deteriorate bone quality through microdamage accumulation. Thus, long-term treatment with risedronate in postmenopausal women with osteoporosis may potentially deteriorate bone quality, although the 7-year effect of risedronate in preventing vertebral fractures has been reported [12]. Strategies to avoid the potential complications of long-term risedronate treatment need to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, it has been reported that suppressed bone turnover by long-term treatment with high-dose risedronate increased microdamage accumulation in the dog rib [11], suggesting long-term and/or high-dose risedronate treatment may deteriorate bone quality through microdamage accumulation. Thus, long-term treatment with risedronate in postmenopausal women with osteoporosis may potentially deteriorate bone quality, although the 7-year effect of risedronate in preventing vertebral fractures has been reported [12]. Strategies to avoid the potential complications of long-term risedronate treatment need to be established.…”
Section: Introductionmentioning
confidence: 99%
“…The mean increase from baseline in lumbar spine BMD over 7 years was 11.5% (P < 0.05). 109 In a large RCT designed to determine hip fracture efficacy, risedronate was shown to reduce hip fracture rates in those with low femoral neck BMD by 40% (P = 0.009) and prior vertebral fractures by 60% (P = 0.003). 110 Nonskeletal clinical risk factors (other than low BMD) did not identify a population that benefited from treatment, although it did identify a population at increased risk of hip fracture.…”
Section: Sogc Clinical Tipmentioning
confidence: 98%
“…Based on studies with alendronate (162) and risedronate, (163,164) patients with osteoporosis will have an antifracture benefit for at least 5 years. However, continued use of BP therapy beyond that time should be reevaluated annually, assessing factors such as BMD, particularly in the hip region, fracture history, newly diagnosed underlying conditions or initiation of other medications known to affect skeletal status, and new research findings in a rapidly evolving field.…”
Section: Medical Management Of Atypical Subtrochanteric/femoral Shaftmentioning
confidence: 99%
“…With regard to risedronate, 7 years of therapy did not further reduce the incidence of vertebral fractures below that observed with 3 and 5 years of therapy. (163) Models to help determine absolute risk of fracture in patients who have already been treated for 4 to 5 years are needed to help guide these decisions.…”
Section: Medical Management Of Atypical Subtrochanteric/femoral Shaftmentioning
confidence: 99%